CLINICAL CASE OF REPLACEMENT OF ENDOTHELIN RECEPTOR ANTAGONIST (BOSENTAN) BY SOLUBLE GUANYLATE CYCLASE STIMULATOR (RIOCIGUAT) IN THE PATIENT WITH PULMONARY ARTERIAL HYPERTENSION - E. A. Devetyarova; A. A. Dyuzhikov; A. A. Dyuzhikova; S. V. Sobin; A. V. Sumin; E. V. Pashchenko (Евразийский Кардиологический Журнал, 2018)
Pulmonary arterial hypertension (PAH) is a life-threatening disease characterized by progressive increase in pulmonary vascular resistance (PVR), higher pulmonary arteries mean pressure (mPAP), decrease in cardiac minute output (CMO) and other hemodynamic, functional and biochemical disorders. Existing PAH therapeutic algorithm, described in the European and Russian clinical guidelines, mainly suggest strategy of sequential combination therapy in the case of inadequate response to initial monotherapy. At this, switching from one PAH-specific drug to another is studied to a lesser extent. At the present similar approach (switching) has already been tested, for example, in switching from one endothelin receptor antagonist (ERA) to another, or from phosphodiesterase type 5 inhibitor (iPDE-5) to soluble guanylate cyclase stimulator (sGC). There are virtually no data about change of monotherapy when drugs target different molecular pathways of vascular tone regulation, in particular, in the pulmonary circulation vessels. This article describes clinical case of female patient with FC III pulmonary arterial hypertension (WHO) switched from therapy by endothelin-1 receptor antagonist (bosentan) to soluble guanylate cyclase stimulator (riociguat). Female, 37 years old, with verified by the right heart catheterization (RHC) diagnosis of idiopathic PAH (iPAH) received PAH-specific monotherapy of bosentan. Due to condition deterioration on the background of bosentan dose increase, medical conference decided to switch this patient to another class of PAH-specific therapy (sGC stimulator riociguat) with consequent follow-up. As a result of such approach positive changes in patient's condition, improvement of hemodynamic parameters, increased tolerance of physical exercise was demonstrated in comparison with previous therapy. This clinical case demonstrates safe and successful transfer from bosentan to riociguat in the patient with idiopathic PAH. Similar tactic for the change of therapy should be studied in further clinical trials.